A Simulation Study of Bulk Cement Product Maritime Tranportation Considering Vessel’s Maintenance - Nurhadi Siswanto; Elisabeth -; Effi Latiffianti (Prosiding International conference on Information Technology and Business (ICITB), 2017)
This study considers an operational decision in the maritime inventory routing problem considering the maintenance schedules of the ships. The problem is to determine the exact number of ships serving to distribute bulk cement product. The problem is complex due to the uncertainties in demand, travel time, loading time, and unloading in each port so that exact optimization methods or mathematical formulations are difficult to do. Therefore, discrete-event simulation method is proposed to solve the problem. In determining the number of vessels to note the external factors that affect the performance of the ship in distributing. One of the activities undertaken to maintain the condition of the ship is maintenance. With the maintenance activities there is a possibility of increasing the number of boats to distribute bulk cement to avoid shortage. The results show that simulation module built can be used to determine the number of vessels and their capacity to determine the optimal number of ships to avoid shortage. From the research work also obtained the effect of maintenance activities in determining the optimal number of vessels. With the arrangement of maintenance schedules made at the time of cement demand is down then the number of ships with a capacity of 3,200-4,500 does not require any additional fleet. But for vessels with a capacity above 4,500 it is necessary to add one fleet of vessels to avoid shortage in unloading portsKeywords: Bulk Cement Product, Maritime Transportation, Disruption of Maintenance, and Discrete Simulation.